2014
DOI: 10.4103/0970-9185.130031
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of hyperbaric ropivacaine versus hyperbaric bupivacaine for elective surgery under spinal anesthesia

Abstract: Background:Recently introduced ropivacaine is 40% less potent than bupivacaine. Ropivacaine made hyperbaric by the addition of dextrose is known to provide reliable spinal anesthesia (SA). This study was designed to compare the clinical efficacy of equal doses of hyperbaric 0.5% ropivacaine with 0.5% bupivacaine for SA.Materials and Methods:Eighty American Society of Anesthesiologists grade I-II patients undergoing elective infraumbilical surgeries under SA were recruited and randomized to receive 3ml of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
4
21
1
Order By: Relevance
“…A similar finding was reported by Kulkarni et al. [17] and Whiteside et al. [18] The hemodynamic parameters were found to be comparable between the groups.…”
Section: Discussionsupporting
confidence: 78%
“…A similar finding was reported by Kulkarni et al. [17] and Whiteside et al. [18] The hemodynamic parameters were found to be comparable between the groups.…”
Section: Discussionsupporting
confidence: 78%
“…(157-234 min). 12,5,9,10 In our study hypotension was seen in most patients (41.7%) in group 1 compared to 18.6% in group 2. In another study bupivacaine group had 42.5% hypotension than in ropivacaine group 25%.…”
Section: Discussionmentioning
confidence: 42%
“…13 This was also proven by many studies. 5,9,14 and easily managed by mephenteramine bolus. Haemodynamic parameters such as heart rate, systolic blood pressure was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results, they concluded that shorter duration of spinal anaesthesia is provided by ropivacaine. 12 Chung et al evaluated the effectiveness and safety of hyperbaric ropivacaine and hyperbaric bupivacaine in providing spinal anaesthesia in patients undergoing elective caesarean delivery. They analyzed 60 patients undergoing elective caesarean surgeries and divided randomly into two study groups.…”
Section: Graph 2: Block Characteristics In Patients In the Two Study mentioning
confidence: 99%